Why you should teach your diabetic patients to chart - Imanzade N (Iran University of Medical Sciences, 1989)
How can patient learn to control their diabetes? The author believes that this important work happen by right training of reporting. Since accurate reporting in the nursing profession is a skill, have you ever though that you teach this skill to their patients?   Reporting about people with chronic disease especially diabetes is beneficial for the following reasons: determination dose of insulin, the amount of food that they can eat, the amount of activity that they can do, avoided from reactions to insulin, to avoid of complications due to hyperglycemia and finally sense of responsibility about themselves and their conditions.